Heterologous Expression of Membrane Proteins Methods and Protocols - Mus-Veteau, Isabelle.; Mus-Veteau, Isabelle. (Methods in Molecular Biology,, 2010)
Membrane proteins play a key role in numerous pathologies such as cancer, cystic fibrosis, epilepsy, hyperinsulinism, and Alzheimer’s disease, yet studies on these and other disorders are hampered by a lack of information about the proteins involved. In Heterologous Expression of Membrane Proteins: Methods and Protocols, expert researchers provide an overview of the different heterologous expression systems available to produce these proteins for structural analysis, helping us to understand how these proteins function, and additionally, how their functions can be modified through drug treatment. Chapters examine membrane protein solubilization, purification, and instability in solution, and investigate the strategies that helped to determine the structure of the first heterologously expressed mammalian membrane proteins. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Far-reaching and innovative, Heterologous Expression of Membrane Proteins: Methods and Protocols, is an essential guide for novice and experienced researchers alike, providing detailed methods for existing expression systems alongside cutting-edge strategies for future use in the field. .